A Review of Tier 2 Interventions Conducted Within Multitiered Models of Behavioral Prevention. (September 2014) - Bruhn, Allison Leigh; Lane, Kathleen Lynne; Hirsch, Shanna Eisner
To support students' academic, behavioral, and social needs, many schools have adopted multitiered models of prevention. Because Tier 3 interventions are costly in terms of time and resources, schools must find efficient and effective Tier 2 interventions prior to providing such intense supports. In this article, we review the literature base on Tier 2 interventions conducted within the context of multitiered prevention models evidencing a Tier 1 behavioral plan. Article selection and coding procedures are described and results are presented. Finally, we summarize our findings of four research questions, reflect on limitations, and offer suggestions for future inquiry.